If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-8=-4(v+19)
We move all terms to the left:
-8-(-4(v+19))=0
We calculate terms in parentheses: -(-4(v+19)), so:We get rid of parentheses
-4(v+19)
We multiply parentheses
-4v-76
Back to the equation:
-(-4v-76)
4v+76-8=0
We add all the numbers together, and all the variables
4v+68=0
We move all terms containing v to the left, all other terms to the right
4v=-68
v=-68/4
v=-17
| 0.6x+0.9=-0.2x-2.3 | | 6(4n-2)=40-2n | | 31=4(u-6)+7u | | x-1=1.48 | | 3/7=2/5x | | 17-s/4=-10s= | | -(j-6)=-3 | | x+3.6=9.2 | | -2y-3-(-4y+5+(-y+2-(3y-1)+2-5))=-(y-4) | | 2=7(w+2)-4w | | 55+26×-1=80x | | 11=6x-1+6x | | -8=-5v+7(v-4) | | -11-2k=1-8k | | 11x-5(2x-1)=5(6-x)+3 | | 7c-(1/3)=(7/9) | | 7x+2x-9=2(4x+8) | | -11-2k=-1-8k | | -7(9n+8)=-31-4n | | -0.67(x+2)=0.17(x+6) | | 90+.50m=50+.60m | | 40(p-4.5)=112 | | .16x+21=x | | 4-8X=9x+20 | | 3h=7(2÷7-3÷7h)-10 | | 8x-9x=-29 | | x/4-5=6-x/4 | | 4/5-x=2 | | 2(3x+2)=x-4 | | 4-8x=9x+8 | | 6x+4x-76=38-9x | | 0.5x-3.5=0.3x-0.5 |